Utilización de la remolacha forrajera (Beta vulgaris) como suplemento alimenticio en cerdas lactantes en la hacienda “Locoa Farms” cantón Latacunga - Alcaciega Chasi, Magaly Adriana (2015)
The research was conducted on the property of LOCOA FARMS, Latacunga Canton, Cotopaxi province, industry LOCOA main street s / n way Palopo Km 51/2 to 2700 m, dry weather snowfall at average annual temperature of 10 -. 17°C. The aim of the study was the evaluation of the fodder beet (Beta vulgaris) as a food supplement of 10% in lactating sows. It was applied he Student T test, 6 lactating sows of the Landrace race where each sow formed an experimental unit which are distributed 3 in each treatment were used, the variables evaluated: feed intake, body condition of sows, growth sucker, sucker body weight, percentage of mortality and morbidity and cost benefit. Feed intake in the treatments T1 and T2 balanced consumed a total of 522 kg each treatment, except that the treatment T2 was added 57.42 kg of Beta vulgaris, T2 being treatment consuming a total of 579, 42 kg between balanced and Beta vulgaris throughout the investigation. Body condition of sows treatment T1 and T2 start with a range of 3, but for T1 exists a decrease in body condition 2; in the treatment T2 is maintained in the range of 3; during the following weeks, which can be said to the Beta vulgaris gives results....